Clostridium Difficile Infection in Ulcerative Colitis: Can Alteration of the Gut-associated Microbiome Contribute to Pouch Failure?. Issue 4 (April 2016) - Skowron, Kinga B.; Lapin, Brittany; Rubin, Michele; Hurst, Roger D.; Rubin, David T.; Hyman, Neil H.; Umanskiy, Konstantin
Abstract : Background: Ulcerative colitis is frequently treated with total proctocolectomy and ileal pouch-anal anastomosis reconstruction. Causes of pouch failure and criteria for improved patient selection remain poorly understood. We aimed to identify risk factors for pouch failure. Methods: We performed a retrospective chart review of patients in a prospectively maintained database. Consecutive patients undergoing ileal pouch-anal anastomosis for inflammatory bowel disease between 2000 and 2010 at our institution were included. The primary outcome was pouch failure, defined as permanent ostomy diversion or pouch excision. Results: Of 417 total patients, 28 (6.7%) patients developed pouch failure. Pouch failure was associated with female gender, anastomotic leak, Crohn's disease of the pouch and preoperative Clostridium difficile colitis. The use of anti–tumor necrosis factor alpha biologics was not associated with pouch failure. Notably, 14.9% of patients were diagnosed with preoperative C. difficile colitis, a factor independently associated with pouch failure (hazard ratio 3.02; 95% confidence interval, 1.23–7.44; P = 0.016). C. difficile colitis did not contribute to failure by increasing the incidence of anastomotic leak but was associated with a diagnosis of Crohn's disease of the pouch (adjusted hazard ratio 2.27 [1.08–4.79]; P = 0.031). Anastomotic leak ( P < 0.001) and pelvic abscess requiring drainage ( P = 0.031) were other independent risk factors for pouch failure. Conclusions: In addition to previously known risk factors, history of preoperative C. difficile colitis was associated with pouch failure after reconstruction, suggesting the need for further study into the role of the gut-associated microbiome in pouch outcomes. Abstract : Article first published online 18 February 2016.